High-temperature-resistant dust-accumulation-resistant photovoltaic module
Patent Information
- Application Number
- CN202610854918.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-14
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]在玻璃涂层方面,主要通过使用疏水或亲水涂层,改变玻璃表面接触角,让雨水带着灰尘从玻璃表面顺畅滚落,但在沙戈荒地区,降雨量比较少,无法实现水珠夹带沙尘滚落的效果,需要针对表面沙尘的清洁及减少停留方向进行优化设计
[0034]1、本发明通过在正面玻璃设置主导流槽与沙丘仿生次导流纹的定向汇聚结构、背面玻璃设置与正面导流槽垂直分布的横向导流槽,搭配与正面主导流槽末端精准适配的边框倒梯形导沙凹槽,形成正反双面、全程无阻碍的沙尘导排通道,同时配合玻璃表面差异化的低附着耐磨涂层,从而彻底摆脱了传统防积尘光伏组件对雨水冲刷清洁的强依赖,实现了仅依靠重力与自然风力即可完成沙尘的定向导排与高效清除,从源头消除了边框积灰死角,大幅降低了沙戈荒少雨环境下的组件积尘率,显著延长组件清洁周期、降低电站运维成本。
Smart Images

Figure CN122995276A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of TOPCon battery module technology, and in particular to a high-temperature resistant and dust-proof photovoltaic module from Shagohuang. Background Technology
[0003] Currently, most dust-proof components in the industry focus on optimizing the glass coating and frame structure design, but lack solutions that simultaneously address the issue of high-temperature heat dissipation.
[0004] Regarding glass coatings, the main approach is to use hydrophobic or hydrophilic coatings to change the contact angle of the glass surface, allowing rainwater to carry dust and roll off smoothly. However, in desert areas, rainfall is relatively low, making it impossible to achieve the effect of water droplets carrying sand and dust off. Therefore, it is necessary to optimize the design to clean the surface sand and dust and reduce the direction of its accumulation.
[0005] Regarding frame structure, several module manufacturers have launched frameless modules and dust-proof modules, mainly focusing on optimizing the frame design. Frameless modules eliminate the frame of the photovoltaic module, preventing dust accumulation and allowing rainwater to carry dust away smoothly from the module edges. They also eliminate the need for gluing and frame assembly steps during production. However, frameless modules are prone to breakage due to edge impacts, have poor installation strength, and have the following drawbacks:
[0006] 1) The short frame is flush with the glass, so that the frame only holds the back glass of the main component. The short frame and the component are connected together by high-strength sealant to ensure the connection strength between the short frame and the component. This method requires a custom frame, production line modification, and the mechanical properties of the component are reduced, and the ability to resist wind and snow is decreased.
[0007] 2) The perforated frame design involves drilling drainage holes on the A side of the traditional frame to guide water and remove dust. However, this method will also cause dust accumulation in areas without drainage holes, and cannot fundamentally solve the problem of dust accumulation at the bottom.
[0008] Therefore, this invention proposes a high-temperature resistant and dust-proof photovoltaic module for desert areas. Summary of the Invention
[0009] One objective of this invention is to propose a high-temperature resistant, dust-resistant photovoltaic module for desert and Gobi areas. This invention can be adapted to the extreme working conditions in desert and Gobi regions. Through the synergistic design of double-surface differentiated flow-guiding glass, a high-wear-resistant frame adapted to guide sand, and an integrated adhesive-heat storage film, it eliminates the dependence of traditional dust-resistant modules on rainwater cleaning, achieving directional drainage and efficient removal of sand and dust. At the same time, it precisely controls the module's operating temperature, mitigates the diurnal temperature difference, and effectively alleviates power attenuation and material aging caused by high temperature and wind and sand erosion. While ensuring the structural reliability of the module, it significantly extends the cleaning cycle, reduces operation and maintenance costs, and improves the long-term power generation stability of the module.
[0010] According to an embodiment of the present invention, a high-temperature resistant and dust-proof photovoltaic module in the desert includes a front glass, a front encapsulating film, a solar cell, a back encapsulating film and a back glass, which are stacked in sequence, and a photovoltaic frame covering the periphery of the glass-cell laminate formed after stacking.
[0011] The front and back glass adopt a double-surface differentiated flow-guiding glass structure. The front glass is the light-receiving surface, and its outer surface facing outward has a main flow channel extending along the length of the glass, as well as sand dune-inspired secondary flow-guiding patterns distributed between adjacent main flow channels. The outer surface of the front glass is also deposited with... Composite superhydrophobic coating;
[0012] The back glass is a non-light-receiving glass, and its outer surface facing the outside is provided with a transverse flow guide groove. The extension direction of the transverse flow guide groove is perpendicular to the extension direction of the main flow guide groove of the front glass. The outer surface of the back glass is also deposited with a fluorocarbon resin anti-wear coating. Both sides of the main flow guide groove and the transverse flow guide groove are provided with sand dune biomimetic secondary flow guide patterns.
[0013] The photovoltaic frame is made of galvanized aluminum-magnesium steel. The outer surface of the frame is uniformly doped with alumina ceramic particles. The frame adopts a double beam cross-section structure. The short frame A side, which corresponds to the end of the front glass flow guide, is provided with a segmented inverted trapezoidal sand guide groove that corresponds one-to-one with the position of the main flow channel of the front glass.
[0014] The front and back glass surfaces are respectively bonded with a front sealing film and a back sealing film. The front and back sealing films adopt a differentiated configuration structure. The front sealing film is a conventional POE film or EPE film, and the back sealing film is a lightweight bonding-heat storage integrated functional EVA film. The functional EVA film uses EVA resin as a matrix and uniformly composites paraffin / expanded graphite phase change heat storage material and nano-silicon carbide thermally conductive filler.
[0015] Furthermore, the front glass is made of ultra-white rolled tempered glass with a thickness of 2.0mm. There are 3 main flow channels, which are evenly distributed in parallel along the length of the glass. The cross-section of each main flow channel is an inverted trapezoidal structure with a channel width of 21mm and a channel depth of 250μm.
[0016] The sand dune-inspired secondary guide pattern is a streamlined groove structure that mimics the wind erosion morphology of sand dunes. The groove depth of the secondary guide pattern is 80μm, and the extension direction of the secondary guide pattern forms an angle of 18° with the horizontal direction. The ends of all the secondary guide patterns extend toward the adjacent main flow groove, which is used to guide the sand and dust on the glass surface to converge directionally into the main flow groove.
[0017] Furthermore, the surface of the front glass deposited with... The composite superhydrophobic coating has a thickness of 80 nm, a Mohs hardness of ≥7, and a water contact angle of >160°. The composite superhydrophobic coating is uniformly applied to the outer surface of the front glass, the inner wall of the main flow channel, and the inner wall of the sand dune biomimetic secondary flow pattern through a vapor deposition process. This is used to reduce the adhesion of sand particles to the glass surface while ensuring the light transmittance and UV aging resistance of the glass.
[0018] Furthermore, the back glass is made of ultra-clear tempered glass with a thickness of 2.0mm, and the transverse guide grooves are evenly distributed in parallel along the width direction of the glass. Each transverse guide groove has a width of 60mm and a depth of 200μm.
[0019] The transverse guide grooves are distributed perpendicularly to the main guide grooves of the front glass at 90°. They are used to guide the sand and dust particles attached to the back glass along the transverse guide grooves to the two sides of the module and discharge them with the help of the air flow on the back of the photovoltaic module, so as to avoid the accumulation of sand and dust on the surface of the back glass.
[0020] Furthermore, the thickness of the fluorocarbon resin anti-wear coating deposited on the outer surface of the back glass is 50 nm, and the coefficient of friction of the coating is ≤0.15. The fluorocarbon resin anti-wear coating is uniformly covered on the outer surface of the back glass and the inner wall of the transverse guide groove by a spray curing process, which is used to improve the resistance of the back glass to wind and sand impact and wear, while reducing the probability of sand and dust particles adhering.
[0021] Furthermore, the thickness of the zinc-aluminum-magnesium steel substrate of the photovoltaic frame is 1.8-2.2mm, the doping amount of alumina ceramic particles in the topcoat on the outer surface of the frame is 20wt%, and the surface hardness of the topcoat after curing is ≥HB300.
[0022] Furthermore, the double-beam cross-section structure of the photovoltaic frame includes an upper beam and a lower beam, with a closed cavity formed between the upper beam and the lower beam to improve the load-bearing performance of the frame;
[0023] There are three segmented inverted trapezoidal sand-guiding grooves, each corresponding to the end position of one of the three main flow channels on the front glass. The width of the groove opening of each inverted trapezoidal sand-guiding groove matches the width of the main flow channel opening. The inner wall slope of the groove forms an angle of 45°-60° with the horizontal direction. It is used to receive sand particles sliding down from the main flow channel and smoothly guide the sand particles to the outside of the component through the slope, so as to avoid sand and dust accumulating at the junction of the frame and the glass to form a dead corner for dust accumulation.
[0024] Furthermore, the raw material composition of the back-side functional EVA film, by mass percentage, is: 76 wt% EVA resin, 23 wt% paraffin / expanded graphite phase change thermal storage material, and 1 wt% nano-silicon carbide thermal conductive powder;
[0025] The EVA resin has a vinyl acetate (VA) content of 28% and a melt flow index of 15 g / 10 min.
[0026] In the paraffin / expanded graphite phase change thermal storage material, the phase change temperature of paraffin is 70℃, and the doping ratio of expanded graphite is 23wt% of the total mass of the phase change material, which is used to prevent paraffin from leaking during the phase change process.
[0027] Furthermore, the temperature control mechanism of the back-side functional EVA film is as follows:
[0028] When the operating temperature of the photovoltaic module rises to 70℃, the paraffin in the encapsulant film reaches the phase change temperature, undergoes a solid-liquid phase change and absorbs a large amount of heat. At the same time, the nano-silicon carbide thermal conductive powder quickly conducts the heat generated by the solar cell to the interior of the encapsulant film, thereby achieving rapid cooling of the module.
[0029] When the operating temperature of the photovoltaic module drops below 60°C, the paraffin in the encapsulant film undergoes a liquid-solid phase change and releases the stored heat, thus smoothing out temperature fluctuations in the module.
[0030] Furthermore, the dual-surface differentiated flow-guiding glass, photovoltaic frame, and differentiated encapsulation film form a synergistic and adaptive integrated system for dust prevention and temperature control;
[0031] The main flow channel at the end of the front glass corresponds one-to-one with the inverted trapezoidal sand-guiding groove of the short frame, forming a continuous and unobstructed sand and dust guiding channel, realizing the smooth guidance of sand and dust from the glass surface to the outside of the component.
[0032] The phase change temperature control system of the back-side functional EVA film can stabilize the module's operating temperature within the optimal tolerance temperature range of the coating and film, reduce the aging rate of the coating and film under high radiation and high temperature conditions in desert areas, and extend the module's service life.
[0033] The beneficial effects of this invention are:
[0034] 1. This invention creates a directional converging structure of a main flow channel and a sand dune-inspired secondary flow pattern on the front glass, and a transverse flow channel on the back glass that is perpendicular to the front flow channel. Combined with a trapezoidal sand-guiding groove on the frame that is precisely adapted to the end of the main flow channel on the front, a double-sided, unobstructed sand and dust guiding channel is formed. At the same time, with a differentiated low-adhesion wear-resistant coating on the glass surface, it completely eliminates the strong dependence of traditional anti-dust photovoltaic modules on rainwater washing and cleaning. It achieves directional guidance and efficient removal of sand and dust by relying solely on gravity and natural wind power, eliminating dead corners for dust accumulation on the frame from the source, significantly reducing the dust accumulation rate of modules in desert and arid environments, significantly extending the module cleaning cycle, and reducing power plant operation and maintenance costs.
[0035] 2. This invention employs a differentiated encapsulation configuration by using a conventional weather-resistant POE / EPE film on the front and a functional EVA film with composite paraffin / expanded graphite phase change thermal storage material and nano-silicon carbide thermal conductive powder on the back. This achieves integrated photovoltaic film bonding and encapsulation with active temperature control without increasing module thickness or sacrificing front insulation protection and weather resistance. The module's operating temperature can be stably controlled below 68°C, while mitigating more than 65% of the day-night temperature difference. This effectively reduces the risk of cell power decay and encapsulation material aging failure caused by high temperatures and extreme temperature cycles in desert areas, significantly improving the module's power generation stability and long-term service life.
[0036] 3. This invention addresses four core pain points of photovoltaic modules in desert and Gobi areas by synergistically adapting three core technologies: differentiated double-surface guiding glass, high wear-resistant photovoltaic frame, and integrated adhesive-thermal storage film. These technologies simultaneously overcome the problems of high wind and sand accumulation, high-temperature power attenuation, easy failure due to extreme temperature differences, and insufficient wind and sand abrasion resistance. This avoids the defects of poor mechanical load performance and easy water seepage at the edges of frameless modules, and also breaks through the limitations of traditional anti-dust accumulation modules where single-point optimization cannot adapt to extreme environments. It achieves a comprehensive and simultaneous improvement in the modules' anti-dust accumulation, high temperature resistance, weather resistance, and structural reliability, perfectly adapting to the extreme working conditions of large-scale photovoltaic bases in desert and Gobi areas. Attached Figure Description
[0037] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings:
[0038] Figure 1 This is a schematic diagram of the front glass of a high-temperature resistant and dust-proof photovoltaic module for desert areas proposed in this invention.
[0039] Figure 2 This is a schematic cross-sectional view of the short and long sides of the front glass of a high-temperature resistant and dust-proof photovoltaic module for desert areas proposed in this invention.
[0040] Figure 3 This is a schematic diagram of the back glass of a high-temperature resistant and dust-proof photovoltaic module for desert areas proposed in this invention.
[0041] Figure 4 This is a schematic cross-sectional view of the short and long sides of the back glass of a high-temperature resistant and dust-proof photovoltaic module for desert areas proposed in this invention.
[0042] Figure 5 This is a schematic diagram of the frame cross-section of a high-temperature resistant and dust-proof photovoltaic module for desert areas proposed in this invention.
[0043] Figure 6This is a schematic diagram of the A-side cross-section of the frame of a high-temperature resistant and dust-proof photovoltaic module for use in desert areas, as proposed in this invention.
[0044] In the image: 1. Front glass; 11. Main flow channel; 12. Sand dune biomimetic secondary flow guide pattern; 13. Composite superhydrophobic coating; 2. Back glass; 21. Horizontal flow guide channel; 22. Fluorocarbon resin wear-resistant coating; 3. Photovoltaic frame; 31. Upper beam; 32. Lower beam; 33. Inverted trapezoidal sand guide groove. Detailed Implementation
[0045] To more clearly illustrate the technical solution of the present invention, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0046] All other embodiments obtained by those skilled in the art based on this embodiment without creative effort are within the protection scope of this invention.
[0047] Example 1
[0048] The high-temperature resistant and dust-proof photovoltaic module for desert and Gobi areas provided in this embodiment is suitable for the extreme climate environment of large-scale ground photovoltaic power stations in desert, Gobi and arid areas. It is specially designed for the double-sided double-glass encapsulation requirements of n-type TOPCon crystalline silicon solar cells and can simultaneously solve the core pain points of existing photovoltaic modules in desert and Gobi scenarios, such as difficulty in cleaning dust accumulation, rapid power decay at high temperatures, easy failure due to large day and night temperature differences, and insufficient resistance to wind and sand abrasion.
[0049] The photovoltaic module includes a front glass 1, a front encapsulating film 3, a solar cell layer, a back encapsulating film and a back glass 2 stacked in sequence, and a photovoltaic frame 3 covering the periphery of the glass-cell laminate formed after lamination and curing.
[0050] The solar cell layer uses n-type TOPCon monocrystalline cells with a size of 182mm×182mm, with a single cell conversion efficiency of ≥26%. It adopts a 12-busbar design and forms 6 cell strings through interconnection ribbons. Each cell string has 12 cells, and the cell strings are connected in parallel through busbars. The overall design is compatible with the finished module size of 2382mm×1134mm.
[0051] See Figure 1-4The front glass 1 and the back glass 2 adopt a double-surface differentiated flow guiding glass structure. The front glass 1 is the light-receiving glass, which is made of 2.0mm thick ultra-white rolled tempered glass. The iron content of the glass matrix is ≤100ppm, the visible light transmittance is ≥91.8%, the surface stress after tempering is ≥90MPa, and the fragmentation state meets the requirements of the national standard GB15733.2-2005. The overall dimensions are 2376mm×1128mm, the diagonal dimension tolerance is ≤±0.5mm, and the thickness tolerance is ≤±0.1mm.
[0052] The outer surface of the front glass 1 facing outward is provided with a main flow channel 11 extending along the length of the glass. The cross-section of the main flow channel 11 is an inverted trapezoidal structure. In this embodiment, there are 3 main flow channels 11, which are evenly distributed in parallel along the length of the glass. The center distance between adjacent main flow channels 11 is 376mm. The width of the opening of a single main flow channel 11 is 21mm, the width of the bottom is 18mm, and the depth is 250μm. The straightness tolerance of the main flow channel 11 is ≤0.3mm / m, and the depth tolerance is ≤±10μm. During the glass calendering process, the above structure is formed in one step by an upper calendering roller with corresponding inverted trapezoidal patterns. The calendering temperature is controlled at 1050℃-1100℃, the calendering roller linear speed is 3.5m / min, and the calendering pressure is 0.6MPa. This ensures that the formed flow channel structure is uniform in size, without deformation or burrs, and avoids damage to the strength of the glass substrate by subsequent etching processes.
[0053] The 18° angle design is perfectly suited to the gravity-driven downward direction of components installed at a conventional 30°-35° angle in the desert region. It can guide the sand and dust particles on the glass surface to converge directionally into the main flow channel 11 under the action of gravity, avoiding the accumulation of sand and dust in the non-channel area of the glass surface.
[0054] The outer surface of the front glass 1 is also deposited with The composite superhydrophobic coating 13 has a total thickness of 80 nm, with the bottom layer being 30 nm thick. A dense layer, with a surface layer 50 nm thick. The porous hydrophobic layer was prepared on the surface of tempered glass using atmospheric pressure chemical vapor deposition. The specific deposition process was as follows:
[0055] The tempered front glass 1 was preheated to 120°C. A mixture of silane and oxygen was then introduced at a flow rate of 20 sccm for silane and 100 sccm for oxygen, with a deposition time of 90 seconds, forming... bottom layer;
[0056] A mixture of tetraisopropyl titanate vapor and nitrogen is then introduced, with a tetraisopropyl titanate vapor flow rate of 15 sccm and a nitrogen carrier gas flow rate of 80 sccm. The deposition time is 120 s, forming... The surface layer is cured by holding it at 150℃ for 30 minutes after deposition.
[0057] The molded composite superhydrophobic coating has a Mohs hardness ≥7, a water contact angle >160°, a roll-off angle <5°, a visible light transmittance loss ≤0.3%, and excellent UV aging resistance after 1000 hours. After ultraviolet irradiation testing, the water contact angle attenuation is ≤2°. The coating is uniformly covered on the outer surface of the front glass 1, the inner wall of the main flow channel 11, and the inner wall of the sand dune biomimetic secondary flow pattern 12 through vapor deposition process, achieving full coverage without dead angles. This can comprehensively reduce the adhesion between sand particles and the glass surface, reducing the contact area between sand particles and the glass surface by more than 85%, while ensuring the light transmittance and UV aging resistance of the glass, making it suitable for the high ultraviolet intensity environment of the Gobi Desert region.
[0058] See Figure 3 , Figure 4 The back glass 2 is a non-light-receiving glass, made of 2.0mm thick ultra-clear tempered glass with an iron content of ≤150ppm, visible light transmittance ≥89%, and surface stress ≥90MPa after tempering. Its overall dimensions are the same as those of the front glass 1, which is 2376mm×1128mm, and its dimensional tolerances are consistent with those of the front glass 1.
[0059] The outer surface of the back glass 2 facing the outside is provided with a transverse guide groove 21. The transverse guide groove 21 is evenly distributed in parallel along the width direction of the glass, and its extension direction is perpendicular to the main guide groove 11 of the front glass 1 at 90°.
[0060] The width of a single transverse guide groove 21 is 60mm, the depth is 200μm, the width of the groove opening is the same as the width of the groove bottom, and the cross-section is a rectangular structure. In this embodiment, a total of 60 transverse guide grooves 21 are set. The center distance between adjacent transverse guide grooves 21 is 39.6mm. The straightness tolerance of the transverse guide grooves 21 is ≤0.3mm / m, and the groove depth tolerance is ≤±10μm. Similarly, in the glass calendering process, it is formed in one go by a lower calendering roller with corresponding texture. The calendering process parameters are the same as those of the front glass 1.
[0061] This vertically distributed structural design can utilize the lateral airflow on the back of the photovoltaic module to guide the sand and dust particles attached to the back glass 2 along the lateral guide groove 21 to the two sides of the module and discharge them. This prevents sand and dust from accumulating on the surface of the back glass 2 and affecting the back-side solar power generation efficiency of the bifacial module. Wind tunnel testing showed that the sand and dust removal rate of the back glass 2 can reach more than 92% under a natural wind speed of 3m / s.
[0062] Both sides of the main flow channel 11 and the transverse flow channel 21 are provided with sand dune-inspired secondary flow patterns. The sand dune-inspired secondary flow patterns 12 are streamlined groove structures that imitate the natural streamline shape of wind-eroded sand dunes in the Gobi Desert. The groove depth of the secondary flow patterns 12 is 80μm, the groove opening width is 1.2mm, and the extension direction of the secondary flow patterns 12 forms an angle of 18° with the horizontal direction. The ends of all secondary flow patterns 12 extend towards the adjacent main flow channel 11 or transverse flow channel 21. The parallel spacing between adjacent secondary flow patterns 12 is 15mm, and the groove depth tolerance of the secondary flow patterns 12 is ≤±5μm. They are also integrally formed synchronously with the main flow channel 11 or transverse flow channel 21 during the calendering process.
[0063] The outer surface of the back glass 2 is also coated with a fluorocarbon resin anti-wear coating 22, with a coating thickness of 50 nm. This coating is prepared on the tempered back glass 2 surface using a high-voltage electrostatic spraying process. The fluorocarbon resin is a polyvinylidene fluoride-hexafluoropropylene copolymer with a number-average molecular weight of 350,000. The solid content of the coating used for spraying is 30%, and the solvent is a mixture of butyl acetate and xylene in a volume ratio of 1:1. The spraying process parameters are as follows:
[0064] The spraying pressure is 0.5 MPa, the distance between the spray gun and the glass surface is 20 cm, the spraying speed is 0.8 m / s, and after spraying, it is cured at 180℃ for 30 min to form a uniform and dense coating.
[0065] The molded fluorocarbon resin anti-wear coating has a friction coefficient ≤0.15, adhesion reaching level 0 in GB / T9286-1998 standard, salt spray resistance ≥3000h, and after 10,000 cycles of wind and sand abrasion test, the coating wear amount is... The coating is evenly applied to the outer surface of the back glass 2 and the inner wall of the transverse guide groove 21, which can significantly improve the resistance of the back glass 2 to wind and sand impact and wear, while reducing the adhesion probability of sand and dust particles, making it suitable for the long-term erosion environment of high wind and sand in desert areas.
[0066] See Figure 5 , Figure 6 The photovoltaic frame 3 is a photovoltaic frame that is adapted to the finished module size of 2382mm×1134mm in this embodiment. It includes two long frames and two short frames, and the long frames and short frames are fixedly connected by 304 stainless steel corner brackets and corner bolts.
[0067] The photovoltaic frame 3 is made of galvanized aluminum-magnesium steel with a substrate thickness of 2.0 mm and a coating thickness of 55 μm. The coating composition is 55% aluminum, 43.5% zinc, and 1.5% magnesium. The coating adhesion is ≥4, the salt spray resistance is ≥5000h, and it has excellent corrosion resistance and shear strength. The yield strength of the formed frame is ≥300MPa and the tensile strength is ≥380MPa.
[0068] The outer surface of the frame is uniformly doped with alumina ceramic particles. The topcoat is a weather-resistant aliphatic polyurethane topcoat, in which the alumina ceramic particles are doped at 20wt%, the average particle size is 5μm, the Mohs hardness is ≥9, the dry film thickness of the topcoat is 35μm, and it is prepared by high-pressure air spraying process. After spraying, it is cured at 160℃ for 20min to form the final shape.
[0069] The surface hardness of the cured topcoat is ≥HB300. After 10,000 wind and sand abrasion tests, the coating integrity rate is ≥98%, and the coefficient of friction of the coating surface is ≤0.16, which can significantly improve the wear resistance and service life of the frame in the high wind and sand environment of the Gobi Desert.
[0070] The photovoltaic frame 3 adopts the industry-standard double-beam cross-section structure, including an upper beam 31 and a lower beam 32. A closed cavity is formed between the upper beam 31 and the lower beam 32 to improve the load-bearing performance of the frame. The upper beam 31 has a height of 7mm, the lower beam 32 has a height of 12mm, and the width of the closed cavity is 10mm. The ends of the upper beam 31 and the lower beam 32 form a laminating slot for engaging the glass laminate. The slot has a width of 7.2mm, which is suitable for the total thickness of 2.0mm front glass 1 + 0.5mm front adhesive film 3 + 0.2mm cell layer 4 + 0.6mm back adhesive film 5 + 2.0mm back glass 2 in this embodiment. Butyl sealant is pre-coated in the slot to achieve a waterproof seal between the laminate and the frame.
[0071] The formed frame can withstand a snow load of 5400Pa and a wind load of 2400Pa, which fully meets the mechanical load requirements of IEC61215-2021 standard.
[0072] The short frame A side of the photovoltaic frame 3, corresponding to the flow guide end of the front glass 1, is provided with segmented inverted trapezoidal sand guide grooves 33 that correspond one-to-one with the positions of the main flow channels 11 of the front glass 1. In this embodiment, the length of the short frame is 1134mm, and there are 3 inverted trapezoidal sand guide grooves 33, which correspond one-to-one with the end positions of the 3 main flow channels 11 of the front glass 1. The groove opening width of each inverted trapezoidal sand guide groove 33 is the same as the groove opening width of the main flow channel 11, which is 21mm. The groove bottom width is 12mm, the groove depth is 3mm, the inner wall slope of the groove forms a 55° angle with the horizontal direction, and the coaxiality tolerance between the center of the groove and the center of the corresponding main flow channel 11 is ≤±1mm, ensuring that the outlet of the main flow channel 11 falls completely into the groove opening range, forming a continuous and unobstructed sand and dust discharge channel.
[0073] The sand-guiding groove 33 is manufactured by CNC milling after the frame is roll-formed. After processing, the inner wall of the groove is passivated to remove burrs and ensure that the inner wall is smooth. It can receive sand particles that slide down from the main flow channel 11 and smoothly guide the sand particles to the outside of the component through the inclined surface, avoiding the accumulation of sand and dust at the junction of the frame and glass to form a dead corner for dust accumulation. This completely solves the industry pain point that the dust accumulation band at the bottom of the traditional frame cannot be removed.
[0074] Front glass 1 and back glass 2 are respectively bonded with front sealing film and back sealing film. The front sealing film and back sealing film adopt a differentiated configuration structure. The front sealing film is a conventional weather-resistant EPE film. In this embodiment, a 0.5mm thick co-extruded EPE film is used, which is co-extruded from two 0.15mm thick layers of EVA and a 0.2mm thick layer of POE in the middle. The VA content of the EVA resin is 28%, and the POE resin is an ethylene-octene copolymer with an octene content of 30%. The film contains 0.4wt% crosslinking agent, 0.3wt% silane coupling agent, 0.2wt% antioxidant, and 0.1wt% UV absorber. It has excellent anti-PID performance, UV aging resistance, and electrical insulation performance, with a volume resistivity ≥ It can meet the encapsulation and protection requirements of the front light-receiving surface.
[0075] The back-side encapsulation film is a lightweight, integrated bonding and thermal storage functional EVA film with a thickness of 0.6mm. This functional EVA film uses an EVA resin matrix as its core, uniformly composited with paraffin / expanded graphite phase change thermal storage material and nano-silicon carbide thermal conductive powder. Its raw material composition, by mass percentage, is as follows:
[0076] The composition includes 76 wt% EVA resin, 23 wt% paraffin / expanded graphite phase change thermal storage material, and 1 wt% nano-silicon carbide thermal conductive powder. It also contains 0.5 wt% tert-butyl peroxide-2-ethylhexyl carbonate crosslinking agent, 0.3 wt% γ-methacryloyloxypropyltrimethoxysilane silane coupling agent, 0.15 wt% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] antioxidant, and 0.05 wt% 2-hydroxy-4-n-octyloxybenzophenone UV absorber.
[0077] The EVA resin has a vinyl acetate (VA) content of 28%, a melt index of 15 g / 10 min, and a Vicat softening point of 72℃, which can ensure the adhesive performance and cross-linking curing performance of the film.
[0078] In paraffin / expanded graphite phase change thermal storage material 52, the paraffin is a straight-chain n-alkane paraffin with 28-32 carbon atoms, a phase change temperature of 70℃, a latent heat of phase change ≥180J / g, and a decomposition temperature ≥250℃. The expanded graphite is worm-like expanded graphite with a specific surface area ≥ The expansion ratio is 250 times, and the doping ratio of expanded graphite is 23wt% of the total mass of the phase change material. Its porous network structure can completely adsorb molten paraffin to prevent paraffin leakage during the phase change process and ensure the stability of the film for long-term use. After 1000 cycles of hot and cold, the latent heat decay rate of phase change is ≤3%.
[0079] The average particle size of the nano-silicon carbide thermal conductive powder 53 is 30 nm, and its thermal conductivity is ≥ It has an extremely high thermal conductivity, which enables rapid and uniform heat transfer from the solar cell to the phase change material, thus avoiding localized hot spots inside the module.
[0080] The back-side functional EVA film is prepared using a twin-screw extrusion casting process. The specific preparation steps are as follows:
[0081] First, expanded graphite and paraffin wax are added to a vacuum impregnation vessel in a certain proportion and impregnated for 2 hours at 100℃ and vacuum degree ≤-0.09MPa to allow the paraffin wax to completely penetrate into the porous structure of the expanded graphite. After cooling to room temperature, the paraffin wax / expanded graphite phase change heat storage material is obtained and then pulverized to 200 mesh for later use.
[0082] Then, EVA resin, pulverized phase change thermal storage material, nano silicon carbide thermal conductive powder, crosslinking agent, coupling agent, antioxidant, and ultraviolet absorber are added to a high-speed mixer in proportion and mixed at high speed for 15 minutes at 80°C and 1200 r / min to obtain a uniformly dispersed mixture.
[0083] The mixture is then fed into a twin-screw extruder. The temperature ranges of each section of the extruder, from the feed inlet to the die head, are set to 90℃, 95℃, 100℃, 105℃, 110℃, and 105℃ respectively. The main extruder speed is 300 r / min. After melting, plasticizing, and filtering, the mixture is fed into a melt pump and cast through a T-die onto a cooling roller. The cooling roller temperature is 15℃. After cooling, shaping, edge trimming, thickness measurement, and winding, a functional EVA film with a thickness of 0.6 mm is obtained.
[0084] The degree of crosslinking of the molded adhesive film is ≥85%, the peel strength to glass is ≥80 N / cm, and the volume resistivity is ≥ It can simultaneously meet the bonding and encapsulation requirements of photovoltaic modules and the temperature control requirements of phase change thermal storage.
[0085] The temperature control mechanism of the back-side functional EVA film is as follows:
[0086] In the high-irradiance environment at noon in the Shago desert region, the irradiance on the surface of the module can reach [amount missing]. As described above, the solar cells generate a large amount of heat during operation, causing the internal temperature of the module to rise rapidly. When the operating temperature of the photovoltaic module rises to 70°C, the paraffin in the encapsulant film reaches the phase change temperature, undergoing a solid-liquid phase change. During this process, it absorbs a large amount of latent heat of phase change; each gram of paraffin can absorb ≥180J of heat. At the same time, the uniformly dispersed nano-silicon carbide thermal conductive powder in the encapsulant film can quickly and evenly conduct the heat generated on the back of the solar cell to the entire encapsulant film layer, allowing the phase change material to fully and evenly absorb heat, thereby rapidly reducing the internal temperature of the module and stabilizing the module's operating temperature below 68°C. This avoids the degradation of the power generation efficiency of crystalline silicon cells caused by high temperatures. The temperature coefficient of crystalline silicon cells is -0.34% / °C. This invention can reduce the module's operating temperature by 8-10°C and increase the relative power generation efficiency by 2.7%-3.4%.
[0087] When the ambient temperature drops significantly at night and the internal temperature of the module falls below 60°C, the paraffin in the encapsulant undergoes a liquid-solid phase change, releasing the latent heat of phase change stored during the day. This provides insulation for the module and significantly mitigates the diurnal temperature difference. Tests show that the diurnal temperature difference mitigation rate of this module is ≥65%, effectively reducing the internal thermal expansion and contraction stress caused by excessive diurnal temperature differences. This avoids problems such as microcracks in the cells, delamination of the encapsulation material, and failure of the frame seal, and significantly improves the long-term operational stability of the module in the extreme temperature difference environment of the desert.
[0088] In this invention, the dual-surface differentiated flow-guiding glass, photovoltaic frame and differentiated encapsulation film form a synergistic and adaptable integrated system for dust prevention and temperature control, achieving comprehensive synergistic effect in structure, function and performance.
[0089] Among them, the end of the main flow channel 11 of the front glass 1 corresponds one-to-one with the inverted trapezoidal sand guiding groove 33 on the short frame A side of the photovoltaic frame 3, forming a continuous and unobstructed sand and dust guiding channel, realizing the smooth guidance and discharge of sand and dust from the glass surface to the final discharge outside the module, with no dust accumulation dead corners, no need to rely on rainwater washing, and only relying on gravity and natural wind to achieve efficient removal of sand and dust.
[0090] Secondly, the horizontal guide groove 21 of the back glass 2 is perpendicularly distributed to the main guide groove 11 of the front glass 1. It can use the airflow on the back to guide the sand and dust to the side, forming a dual-sided anti-dust accumulation effect with the sand guiding structure on the front, thus comprehensively solving the dust accumulation problem on both sides of the module.
[0091] Meanwhile, the phase change temperature control system of the back-side functional EVA film can stabilize the module's operating temperature within the optimal tolerance temperature range of the coating and film, avoiding problems such as coating aging, film yellowing, and decreased cross-linking caused by the high radiation and high temperature environment in the desert region. The service life of the composite superhydrophobic coating is extended from the conventional 5 years to more than 15 years, and the aging resistance of the encapsulating film can fully match the 25-year design service life of the component.
[0092] The long-term stability of the coating and film can further ensure the dust-proof effect and encapsulation reliability of the components, forming a positive cycle of "dust-proof - stable temperature - long life - high power generation", which is perfectly adapted to the extreme climate environment of the desert region.
[0093] The overall assembly and manufacturing process of the photovoltaic module in this embodiment is as follows:
[0094] The first step is to cut and prepare the materials. Cut the front glass 1, back glass 2, front sealing film 3 and back sealing film according to the design dimensions. The cutting size tolerance is ≤ ±0.5mm. After cutting, the edges of the glass are ground and chamfered. The chamfer size is 0.2mm×45° to avoid stress concentration at the edges.
[0095] The second step is the battery string preparation. 182mm×182mm n-type TOPCon monocrystalline solar cells are connected in series to form battery strings by interconnecting solder strips. The soldering temperature is 360℃ and the soldering time is 80ms. Each string contains 12 solar cells and there are 6 strings in total. After the soldering is completed, EL test is performed to remove defective battery strings with poor soldering or microcracks.
[0096] The third step is to lay the layers in sequence on the stacking platform, following the order of front glass 1, front encapsulating film 3, solar cell layer, back encapsulating film, and back glass 2. During the laying process, ensure that each layer is centered and aligned, with a layer offset of ≤ ±0.3mm, and no wrinkles or bubbles. The battery strings are connected in parallel and welded through busbars. After welding, positive and negative leads are led out.
[0097] The fourth step is lamination and curing. The laid-up laminate is placed in a dual-chamber laminator. First, a vacuum is drawn in the vacuum chamber with a vacuum degree ≤100Pa and a vacuum time of 360s. Then, it enters the lamination chamber with a lamination temperature of 145℃, a lamination pressure of 45MPa, and a lamination curing time of 15min to complete the lamination process and obtain the photovoltaic laminate.
[0098] The fifth step is edge trimming and testing. The laminated parts are trimmed to remove excess adhesive waste. Then, EL appearance test and IV power test are performed to reject defective products with hidden cracks, poor soldering, misalignment, or substandard power.
[0099] Step 6: Frame assembly. Apply a 1.2mm thick layer of butyl sealant and polyurethane structural adhesive (80g / m²) evenly to the laminating slots of the cut long and short frames. Assemble the frames around the perimeter of the laminate. During assembly, ensure precise alignment of the three inverted trapezoidal sand-guiding grooves 33 on side A of the short frame with the ends of the three main flow channels 11 on the front glass 1, ensuring the outlets of the main flow channels 11 fall completely within the groove openings. After assembly, use 304 stainless steel angle brackets and M5 angle bolts to connect and secure the long and short frames. The angle bolt torque is... Allow the structural adhesive to cure completely at room temperature for 24 hours.
[0100] Step 7: Junction box installation. Install the photovoltaic junction box at the corresponding position on the back of the module. Solder the positive and negative leads of the module to the diodes inside the junction box. After soldering, apply 150g of glue for curing at room temperature for 4 hours. Step 8: Finished product testing. Perform power testing, insulation testing, wet leakage current testing, and EL final inspection on the assembled module. After passing the tests, the finished product, the Shagohuang high-temperature resistant and dust-proof photovoltaic module, is obtained.
[0101] To further verify the technical effects of the present invention, the following embodiments and comparative examples are provided, wherein Embodiment 1 is the optimal embodiment of the present invention, and the technical solution is completely consistent with the above content;
[0102] Example 2
[0103] The front glass 1 has a main flow channel 11 with a depth of 200μm, the sand dune biomimetic secondary flow guiding pattern 12 has an angle of 15° with the horizontal direction, the inner wall slope of the inverted trapezoidal sand guiding groove 33 has an angle of 45° with the horizontal direction, and the phase change material content in the back encapsulation film is 20wt%. The rest of the technical solutions are the same as in Example 1.
[0104] Example 3
[0105] The front glass 1 has a main flow channel 11 with a depth of 300μm, the sand dune biomimetic secondary flow guiding pattern 12 has an angle of 20° with the horizontal direction, the inner wall slope of the inverted trapezoidal sand guiding groove 33 has an angle of 60° with the horizontal direction, and the phase change material content in the back encapsulation film is 25wt%. The rest of the technical solutions are the same as in Example 1.
[0106] Comparative Example 1 is a conventional commercial photovoltaic module used in the desert area, employing... The conventional ultra-clear glass with hydrophobic coating has no flow channel structure, uses a conventional galvanized aluminum-magnesium steel frame, has no sand guide groove, uses a conventional EPE front and back isomorphic encapsulation film, has no phase change heat storage material, and the rest of the structure is the same as in Example 1.
[0107] Comparative Example 2 is a commercial frameless anti-dust photovoltaic module, which uses conventional ultra-white glass with a hydrophilic coating, has no channel structure, eliminates the frame design, uses conventional POE encapsulation film, and the rest of the structure is the same as Example 1;
[0108] Comparative Example 3 is a dust-proof component with only an optimized frame. It uses conventional ultra-white glass, has no drainage channel structure, uses a galvanized aluminum-magnesium steel frame with sand-guiding grooves, and uses conventional EPE encapsulation film. The rest of the structure is the same as Example 1.
[0109] Comparative Example 4 is a temperature control component with only optimized adhesive film. It uses conventional ultra-white glass, has no flow channel structure, uses a conventional galvanized aluminum-magnesium steel frame, and uses EVA adhesive film with phase change material. The rest of the structure is the same as in Example 1.
[0110] The photovoltaic modules of Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests. The test environment simulated the extreme climatic conditions of the Sakhalin region. The test items and methods are as follows:
[0111] Dust accumulation rate test: The component was installed at a 32° angle in a dust test chamber, using ISO12103-1A4 level test dust, with a dust concentration of [missing information]. With a wind speed of 8 m / s, dust was continuously blown for 24 hours. The maximum power of the components before and after dust blowing was tested, and the power attenuation rate was calculated as the dust accumulation rate. Dust accumulation rate = (initial power - power after dust blowing) / initial power × 100%;
[0112] Component operating temperature test: In an environmental simulation chamber, the irradiance was set to [value missing]. The ambient temperature was 45℃, and the irradiation was continuous for 4 hours. The average operating temperature of the internal cells of the module was tested using thermocouples.
[0113] Day and night temperature difference suppression rate test: The ambient temperature is set to cycle between -20℃ and 70℃ for 24 hours. The highest and lowest temperatures inside the component are tested, and the temperature difference suppression rate is calculated. Temperature difference suppression rate = (temperature difference of control group - temperature difference of experimental group) / temperature difference of control group × 100%. The control group is the comparative example 1.
[0114] Wind and sand abrasion resistance test: A wind and sand abrasion tester was used, with a wind speed of 18 m / s and a sand and dust concentration of [missing information]. The coating was continuously tested 10,000 times to assess its wear and integrity.
[0115] Mechanical load performance test: The maximum snow load bearing capacity of the component is tested in accordance with IEC61215-2021 standard;
[0116] Power attenuation test after aging: DH1000 damp heat aging test, UV1000 ultraviolet aging test, and TC200 hot and cold cycle test were conducted in accordance with IEC61215-2021 standard to test the maximum power attenuation rate before and after aging.
[0117] Performance test results show that the 24-hour dust accumulation rate of Example 1 of the present invention is only 1.2%, which is much lower than that of Comparative Example 1 (8.7%), Comparative Example 2 (5.3%), Comparative Example 3 (4.2%) and Comparative Example 4 (9.1%), and the dust accumulation prevention effect is improved by more than 70%.
[0118] The average operating temperature of the battery cell in Example 1 was 66.2℃, which was 12.4℃ lower than that of Comparative Example 1 (78.6℃). The diurnal temperature range reduction rate reached 68.2%, which can effectively reduce the extreme diurnal temperature range in the desert region.
[0119] Example 1: After wind and sand abrasion, the coating integrity rate was 98.7%, the maximum snow load bearing capacity reached 5600Pa, and the cumulative power attenuation rate after aging was only 1.8%. The wind and sand abrasion resistance, mechanical load performance and aging resistance are significantly better than the existing technical solutions.
[0120] The performance of Examples 2 and 3 is also far superior to that of the comparative examples, verifying the stability and universality of the technical solution of the present invention within the parameter range, and fully demonstrating that the present invention can perfectly achieve the design goals of dust prevention, high temperature resistance, and high reliability in desert environments.
[0121] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A high-temperature resistant and dust-proof photovoltaic module for desert areas, characterized in that, It includes a front glass (1), a front encapsulating film, a solar cell, a back encapsulating film and a back glass (2) stacked in sequence, and a photovoltaic frame (3) covering the outer periphery of the glass-cell laminate formed after stacking. The front glass (1) and the back glass (2) adopt a double-surface differentiated flow guiding glass structure, wherein the front glass is the light-receiving glass, and its outer surface facing the outside is provided with a main flow groove (11) extending along the length of the glass. The outer surface of the front glass is also deposited with Composite superhydrophobic coating (13); The back glass (2) is a non-light-receiving glass, and its outer surface facing the outside is provided with a transverse flow guide groove (21). The extension direction of the transverse flow guide groove (21) is perpendicular to the extension direction of the main flow guide groove (11) of the front glass (1). The outer surface of the back glass (2) is also deposited with a fluorocarbon resin anti-wear coating (22). Both sides of the main flow guide groove (11) and the transverse flow guide groove (21) are provided with sand dune biomimetic secondary flow guide patterns (12). The photovoltaic frame (3) is made of galvanized aluminum-magnesium steel. The outer surface of the frame is uniformly doped with alumina ceramic particles. The frame adopts a double beam cross-section structure. The short frame A side corresponding to the flow guide end of the front glass (1) is provided with a segmented inverted trapezoidal sand guide groove (33) that corresponds one-to-one with the position of the main flow channel (11) of the front glass (1). The front glass (1) and the back glass (2) are respectively bonded with a front sealing film and a back sealing film. The front sealing film and the back sealing film adopt a differentiated configuration structure. The front sealing film is a conventional POE film or EPE film, and the back sealing film is a lightweight bonding-heat storage integrated functional EVA film. The functional EVA film uses EVA resin as the matrix and uniformly composites paraffin / expanded graphite phase change heat storage material and nano silicon carbide thermal conductive filler.
2. The high-temperature resistant and dust-proof photovoltaic module for desert areas according to claim 1, characterized in that, The front glass (1) is made of ultra-white rolled tempered glass with a thickness of 2.0mm. There are 3 main flow channels (11) that are evenly distributed in parallel along the length of the glass. The cross-section of each main flow channel (11) is an inverted trapezoidal structure with a channel width of 21mm and a channel depth of 250μm. The sand dune biomimetic secondary guide pattern (12) is a streamlined groove structure that imitates the wind erosion shape of sand dunes. The groove depth of the sand dune biomimetic secondary guide pattern (12) is 80μm. The extension direction of the sand dune biomimetic secondary guide pattern forms an angle of 18° with the horizontal direction. The ends of all sand dune biomimetic secondary guide patterns extend toward the adjacent main flow groove (11) to guide the sand and dust on the glass surface to converge in the main flow groove.
3. The high-temperature resistant and dust-proof photovoltaic module for desert areas according to claim 2, characterized in that, The outer surface of the front glass (1) is deposited with The composite superhydrophobic coating (13) has a thickness of 80 nm, a Mohs hardness of ≥7, and a water contact angle of >160° on the surface of the coating. The composite superhydrophobic coating (13) is uniformly covered on the outer surface of the front glass (1), the inner wall of the main flow channel (11), and the inner wall of the sand dune biomimetic secondary flow pattern (12) by vapor deposition process. It is used to reduce the adhesion of sand particles to the glass surface, while ensuring the light transmittance and UV aging resistance of the glass.
4. The high-temperature resistant and dust-proof photovoltaic module for desert areas according to claim 1, characterized in that, The back glass (2) is made of ultra-white tempered glass with a thickness of 2.0mm. The transverse guide grooves (21) are evenly distributed in parallel along the width direction of the glass. The width of each transverse guide groove is 60mm and the depth is 200μm. The transverse guide groove (21) is perpendicular to the main guide groove (11) of the front glass (1) at 90°. It is used to guide the sand and dust particles attached to the back glass along the transverse guide groove (21) to the two sides of the module and discharge them with the help of the air flow on the back of the photovoltaic module, so as to avoid the accumulation of sand and dust on the surface of the back glass.
5. A high-temperature resistant and dust-proof photovoltaic module for desert areas according to claim 4, characterized in that, The thickness of the fluorocarbon resin anti-wear coating (22) deposited on the outer surface of the back glass (2) is 50 nm, and the coefficient of friction of the coating is ≤0.
15. The fluorocarbon resin anti-wear coating (22) is uniformly covered on the outer surface of the back glass (2), the transverse guide groove (21) and the inner wall of the sand dune biomimetic secondary guide pattern (12) by spray curing process, which is used to improve the anti-wind and sand impact wear performance of the back glass (2) and reduce the adhesion probability of sand and dust particles.
6. The high-temperature resistant and dust-proof photovoltaic module for desert areas according to claim 1, characterized in that, The thickness of the zinc-aluminum-magnesium steel substrate of the photovoltaic frame (3) is 1.8-2.2mm, the doping amount of alumina ceramic particles in the topcoat on the outer surface of the frame is 20wt%, and the surface hardness of the topcoat after curing is ≥HB300.
7. A high-temperature resistant and dust-proof photovoltaic module for desert areas according to claim 6, characterized in that, The photovoltaic frame (3) has a double beam cross-section structure including an upper beam (31) and a lower beam (32), and a closed cavity is formed between the upper beam (31) and the lower beam (32) to improve the load resistance performance of the frame; There are three segmented inverted trapezoidal sand guiding grooves (33), which correspond one-to-one with the end positions of the three main flow channels (11) of the front glass (1). The groove width of each inverted trapezoidal sand guiding groove (33) matches the groove width of the main flow channel (11). The inner wall slope of the groove forms an angle of 45°-60° with the horizontal direction. It is used to receive sand particles that slide down from the main flow channel (11) and smoothly guide the sand particles to the outside of the component through the slope, so as to avoid the sand and dust accumulating at the junction of the frame and the glass to form a dead corner for dust accumulation.
8. The high-temperature resistant and dust-proof photovoltaic module for desert areas according to claim 1, characterized in that, The raw material composition of the back-side functional EVA film, by mass percentage, is: 76 wt% EVA resin, 23 wt% paraffin / expanded graphite phase change thermal storage material, and 1 wt% nano-silicon carbide thermal conductive powder; The EVA resin has a vinyl acetate (VA) content of 28% and a melt flow index of 15 g / 10 min. In the paraffin / expanded graphite phase change thermal storage material, the phase change temperature of paraffin is 70℃, and the doping ratio of expanded graphite is 23wt% of the total mass of the phase change material, which is used to prevent paraffin from leaking during the phase change process.
9. A high-temperature resistant and dust-proof photovoltaic module for desert areas according to claim 8, characterized in that, The temperature control mechanism of the back-side functional EVA film is as follows: When the operating temperature of the photovoltaic module rises to 70℃, the paraffin in the encapsulant film reaches the phase change temperature, undergoes a solid-liquid phase change and absorbs a large amount of heat. At the same time, the nano-silicon carbide thermal conductive powder quickly conducts the heat generated by the solar cell to the interior of the encapsulant film, thereby achieving rapid cooling of the module. When the operating temperature of the photovoltaic module drops below 60°C, the paraffin in the encapsulant film undergoes a liquid-solid phase change and releases the stored heat, thus smoothing out temperature fluctuations in the module.
10. A high-temperature resistant and dust-proof photovoltaic module for desert areas according to claim 1, characterized in that, The end of the main flow channel (11) of the front glass (1) corresponds one-to-one with the inverted trapezoidal sand guide groove (33) of the short frame of the photovoltaic frame (3), forming a continuous and unobstructed sand and dust guide channel, realizing the smooth guide of sand and dust from the glass surface to the outside of the module. The phase change temperature control system of the back-side functional EVA film can stabilize the module's operating temperature within the optimal tolerance temperature range of the coating and film, reduce the aging rate of the coating and film under high radiation and high temperature conditions in desert areas, and extend the module's service life.